DIVERSITY AND DISTRIBUTION OF FROGS IN LAKE IPB DRAMAGA CAMPUS - Ribut, Amat; Auliaputri, Tazkiah; Pratiwi, Intan Ratu; Sese, Moh. Reza; Perwitasari-Farajallah, Dyah (Masyarakat Zoologi Indonesia, 2024)
Indonesia has two of the three amphibian orders, Gymnophiona and Anura. Frogs in Indonesia have ten families. In West Java, there are 28 Anura species from six families. In general, frog habitats are very diverse and can be found in urban areas. However, the distribution in the IPB Dramaga campus, especially in the lake ecosystem is still unknown. Therefore, this research aims to determine the diversity and distribution of the Anura order in the Lake Ecosystem of IPB Dramaga. The method used is the Visual Encounter Survey (VES). The research locations are the three lakes ecosystem at IPB Dramaga (SDGs, Inspirasi Lake, LSI). This research recorded eight species, including Duttaphrynus melanostictus, Ingerophrynus biporcatus, Fejervarya cancrivora, Limnonectes macrodon, Hylarana erythraea, Amnirana nicobariensis, Microhyla achatina, and Polypedates leucomystax. Species D. melanostictus and F. cancrivora are distributed throughout the lake. This study recorded that the Shannon-Wiener diversity in the IPB Dramaga Lake ecosystem (SDGs, Telaga Inspirasi, LSI) was in the medium category (1.28–1.71). Brillouin Diversity Index is in the high category (1.18– 1.50). The evenness index (0.82–0.92) was close to even. Simpson's Dominance Index (0.21–0.30) and Margalef's Species Richness (1.17–1.91) were low.